Low-cost technology for fish monitoring applied to the fishing of two species of pacu in Amazonas, Brazil - Lourenço, Igor Hister (2020)
The present study aimed to investigate the “pacu” species’ commercialized in the “Colônia dos Pescadores Z-31” in the municipality of Humaitá, Amazonas State, from May 2018 to April 2019. For this purpose, we developed a method for raising a diary database in the colony, obtaining variables such as production, effort, catch per unit effort (CPUE), fishing spots, amongst others. We have identified two species of “pacu” - Mylossoma aureum and M. duriventre - with productions of 10.5 and 9.5 tonnes respectively which generated an income of U$ 22,173.00. Captures occurred mostly randomly, due to the region’s fishing characteristics although the CPUE was higher when compared to bigger cities. We could also find evidence over their migratory cycles from a correlation between the catching sites and the period, where: i) during the falling water (May to July), the “pacus” start to leave the streams and concentrate in lakes; ii) during the dry season (August to October), the “pacus” perform a second migratory cycle, leaving streams and lakes and going to rivers; iii) finally, during the rising water, “pacus” once again move to small streams. The generated information can be used in fishing strategies in the region, reducing costs with inputs.